Physical Characteristics and Antioxidant Potential of Star Anise (Illicium verum Hook f.) Essential Oil Nanoemulgel as a Natural Cosmetic - Widyowati, Retno; Sari, Trisiyana Sholika; Munandar, Tristiana Erawati (Brawijaya University, 2025)
Background : Oxidative stress caused by reactive oxygen species (ROS) is a major contributor to skin damage. Illicium verum (star anise) essential oil is rich in trans-anethole, a compound reported as the dominant component (over 88%) in previous GC-MS studies. Trans-anethole possesses potent antioxidant properties; however, its lipophilic nature limits its solubility and topical bioavailability. Objective : This study aimed to develop and characterize a nanoemulgel formulation Illicium verum essential oil and to evaluate its antioxidant activity for potential application as a natural antioxidant. Methods : Essential oil (1% w/v) was extracted by steam distillation and formulated into a nanoemulgel using a self-nanoemulsifying technique, which involves the spontaneous formation of nano-sized droplets upon mixing the oil phase with surfactants (Tween 80 and Span 80 in a 6:1 ratio) under agitation. The resulting nanoemulsion was incorporated into a hydrogel base using 1% Carbopol 940, a hydrophilic polymer that forms a three-dimensional network capable of retaining water, creating a gel-like texture suitable for topical application. The formulation was evaluated for pH, viscosity, droplet size, polydispersity index (PDI), zeta potential, and stability. Antioxidant activity was determined using the DPPH assay, with ascorbic acid as the positive control then analyzed using one-way ANOVA. Results : The nanoemulgel showed pH 6.03 ± 0.28, viscosity 13164 ± 2.65 cP, droplet size 188.5 ± 0.49 nm, PDI 0.1638 ± 0.15, and zeta potential -41.09 ± 1.59 mV indicating good physical stability and homogeneity. It passed centrifugation and spreadability tests and exhibited a semi-transparent appearance with a smooth texture and pleasant aroma. According to established criteria (Itam et al., 2021), the IC₅₀ value of the nanoemulgel (85.03 ± 0.75 µg/mL) demonstrated moderate antioxidant activity, while the essential oil alone exhibited strong activity (IC₅₀ = 50.89 ± 0.55 µg/mL), and ascorbic acid, used as a positive control, showed very strong activity (IC₅₀ = 2.59 ± 0.28 µg/mL). Statistical analysis confirmed a significant difference between groups (p < 0.05). Conclusions : The nanoemulgel formulation demonstrated favorable physical properties, including skin-compatible pH, suitable viscosity, nano-sized droplets, low polydispersity, and high colloidal stability. It retained moderate antioxidant activity, supporting its potential application as a natural antioxidant cosmetic. Further in vivo studies are recommended to validate its clinical efficacy.